A Rare case of papillary carcinoma in branchial cleft cyst - Das , A K; Shelly, Divya; Jadhav, Sujata; Pitale, Devdatt (Tropical Journal of Pathology and Microbiology, 2025)
Anomalies of branchial cyst are rare diseases of head and neck region. Confirmation el definite pathology is always challenging for clinicians. Ectopic thyroid tissue is ubiquitous in the body and branchial cleft cyst a congenital abnormality can rarely harbor thyroid tissue in cyst. Primary pupillary thyroid carcinoma (PTC) inside ectopic thyroid tissue is extremely rare. We report a very rare case of PTC incidentally arising in a brunchial cyst cleft.